In-situ measurement of electrode kinetics in porous electrode for vanadium flow batteries using symmetrical cell design. (15th August 2020) - Zhang, Kaiyue; Xiong, Jing; Yan, Chuanwei; Tang, Ao
Graphical abstract: Highlights: Electrode kinetics in porous electrode is determined by a symmetric cell design. Polarization curve and high frequency resistance are obtained on the symmetric cell. Activation polarization is calculated by polarization analysis in a symmetric cell. Tafel fitting yields rate constant and transfer coefficient in porous felt electrode. Full cell simulation and experiment validate the feasibility of the proposed method. Abstract: Electrode kinetics are crucial to electrochemical performance of vanadium flow battery. However, existing studies on electrode kinetics are mostly performed in ex-situ conditions based on planar electrodes, so the obtained rate constant can neither reflect the kinetics in practically used porous electrode nor be used to predict the activation polarizations of a real flow cell. To address this limitation, an in-situ measurement of electrode kinetics in porous electrode is conducted in this study by a symmetrical cell design for vanadium flow battery. For both V 2+ /V 3+ and VO 2+ /VO2 + couples, the activation polarization as a function of current density is firstly acquired on the symmetrical cell through measurements of polarization curve, high frequency resistance and local mass transfer coefficient, followed by Tafel fitting that yields both rate constant and transfer coefficient. Based on kinetic parameters of both V 2+ /V 3+ and VO 2+ /VO2 +, the simulated full cell activation polarizations coincide well with the full cell experimental result. By further comparing to simulation results using reported kinetic parameters determined from planar electrodes, the reliability of the proposed method is further highlighted. The electrode evaluation is much more involved than Tafel polarization and stack design is not treated in this contribution.